Catching Up with the Joneses: Heterogeneous Preferences and the Dynamics of Asset Prices - Chan, Yeung Lewis; Kogan, Leonid (Journal of Political Economy, 2002)
We analyze a general equilibrium exchange economy with a continuum of agents who have “catching up with the Joneses” preferences and differ only with respect to the curvature of their utility functions. While individual risk aversion does not change over time, dynamic redistribution of wealth among the agents leads to countercyclical time variation in the Sharpe ratio of stock returns. We show that both the conditional risk premium and the return volatility are negatively related to the level of stock prices. Therefore, our model exhibits many of the empirically observed properties of aggregate stock returns, for example, patterns of autocorrelation in returns, the “leverage effect” in return volatility, and long‐horizon return predictability.